Caste : the origins of our discontents - Wilkerson, Isabel (New York : Random House, 2020)
""As we go about our daily lives, caste is the wordless usher in a darkened theater, flashlight cast down in the aisles, guiding us to our assigned seats for a performance. The hierarchy of caste is not about feelings or morality. It is about power--which groups have it and which do not." In this brilliant book, Isabel Wilkerson gives us a masterful portrait of an unseen phenomenon in America as she explores, through an immersive, deeply researched narrative and stories about real people, how America today and throughout its history has been shaped by a hidden caste system, a rigid hierarchy of human rankings. Beyond race, class, or other factors, there is a powerful caste system that influences people's lives and behavior and the nation's fate. Linking the caste systems of America, India, and Nazi Germany, Wilkerson explores eight pillars that underlie caste systems across civilizations, including divine will, bloodlines, stigma, and more. Using riveting stories about people--including Martin Luther King, Jr., baseball's Satchel Paige, a single father and his toddler son, Wilkerson herself, and many others--she shows the ways that the insidious undertow of caste is experienced every day. She documents how the Nazis studied the racial systems in America to plan their out-cast of the Jews; she discusses why the cruel logic of caste requires that there be a bottom rung for those in the middle to measure themselves against; she writes about the surprising health costs of caste, in depression and life expectancy, and the effects of this hierarchy on our culture and politics. Finally, she points forward to ways America can move beyond the artificial and destructive separations of human divisions, toward hope in our common humanity. Beautifully written, original, and revealing, Caste: The Origins of Our Discontents is an eye-opening story of people and history, and a reexamination of what lies under the surface of ordinary lives and of America life today"--
Includes bibliographical references and index.
HB
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Caste -- United States; Social stratification -- United States; Ethnicity -- United States; Power (Social sciences) -- United States; United States -- Race relations